Visual artificial grammar learning in dyslexia: A meta-analysis. (November 2017) - van Witteloostuijn, Merel; Boersma, Paul; Wijnen, Frank; Rispens, Judith
Graphical abstract: The present meta-analysis shows that, if the 13 selected studies constitute a random sample, individuals with dyslexia perform worse on average than non-dyslexic individuals (average weighted effect size = 0.46, 95% CI [0.14 … 0.77], p = 0.008), with a larger effect in children than in adults ( p = 0.041; average weighted effect sizes 0.71 [sig.] versus 0.16 [non-sig.]). However, the presence of a publication bias indicates the existence of missing studies that may well null the effect. Highlights: A meta-analysis of 13 visual artificial grammar learning studies in dyslexia. Dyslexia is characterized by artificial grammar learning difficulties ( g = 0.46). These difficulties may be more pronounced in children than in adults with dyslexia. An observed publication bias suggests that missing studies may well null the effect. Abstract: Background: Literacy impairments in dyslexia have been hypothesized to be (partly) due to an implicit learning deficit. However, studies of implicit visual artificial grammar learning (AGL) have often yielded null results. Aims: The aim of this study is to weigh the evidence collected thus far by performing a meta-analysis of studies on implicit visual AGL in dyslexia. Methods and procedures: Thirteen studies were selected through a systematic literature search, representing data from 255 participants with dyslexia and 292 control participants (mean age range: 8.5–36.8 years old). Results: If the 13 selected studies constitute a random sample, individuals with dyslexia perform worse on average than non-dyslexic individuals (average weighted effect size = 0.46, 95% CI [0.14 … 0.77], p = 0.008), with a larger effect in children than in adults (p = 0.041; average weighted effect sizes 0.71 [sig.] versus 0.16 [non-sig.]). However, the presence of a publication bias indicates the existence of missing studies that may well null the effect. Conclusions and implications: While the studies under investigation demonstrate that implicit visual AGL is impaired in dyslexia (more so in children than in adults, if in adults at all), the detected publication bias suggests that the effect might in fact be zero.